مقياس تشخيصي لقياس وعي معلمات الروضة بالإسعافات الأولية للطفل - الرزاز، مها أحمد محمد (جامعة الإسكندرية - كلية رياض الأطفال, 2015)
تناولت هذه الدراسة موضوعاً من موضوعات رياض الأطفال الذي يحاول تقديم خدمات لمعلمات هذه المرحلة بما يقدمه موضوع التشخيص من مساعدات للكشف عن وعي معلمات الروضة بالإسعافات الأولية للطفل على وجه الخصوص، من خلال إيجاد أداة أو مقياس تشخيصي يساهم في تحسين مستوى كفاية خدمات التشخيص والتقييم وتحقيق جودة الأداء في مجال الكشف عن أعراض السلوك الذي يستهدف معلمات هذه المرحلة. وقد هدفت الدراسة إلى بناء (تصميم) مقياس تشخيصي لقياس وعي معلمات الروضة بالإسعافات الأولية للطفل على عينة من 60 معلمة من معلمات رياض الأطفال في محافظة الغربية. وتوصلت إلى ضبط الخصائص السيكومترية للمقياس من صدق وثبات ليكون بذلك قابلا للاستخدام في الميدان الذي صمم لأجله.
This study addressed the topic of the kindergarten, which is trying to provide services for teachers this stage as provided by the subject of the diagnostic aid for the detection of awareness of the kindergarten teachers first aid to the child, in particular, through the creation of a tool or a diagnosis of scale contribute to improving the efficiency of the diagnosis, evaluation and achieve quality of service level performance in the field of detection of the symptoms of behavior which aims parameters this stage to know. The study aimed to build Design Diagnostic Scale to measure the awareness of the kindergarten teachers first aid to the child on a sample of 60 teacher of kindergarten teachers in the western province. Reached to adjust the psychometric properties of the scale of the validity and reliability making it usable in the field, which was designed for him.
Keywords: رياض الأطفال -- معلمات الروضة -- الإسعافات الأولية -- الوعي الصحي -- المقاييس التشخيصية